The CDK inhibitor AT7519M in patients with relapsed or refractory chronic lymphocytic leukemia (CLL) and mantle cell lymphoma. A Phase II study of the Canadian Cancer Trials Group. Issue 6 (3rd June 2017) - Seftel, Matthew D.; Kuruvilla, John; Kouroukis, Tom; Banerji, Versha; Fraser, Graeme; Crump, Michael; Kumar, Rajat; Chalchal, Haji I.; Salim, Muhammad; Laister, Rob C.; Crocker, Susan; Gibson, Spencer B.; et al.
Abstract: AT7519M is a small molecule inhibitor of cyclin-dependent kinases 1, 2, 4, 5, and 9 with in vitro activity against lymphoid malignancies. In two concurrent Phase II trials, we evaluated AT7519M in relapsed or refractory chronic lymphocytic leukemia (CLL) and mantle cell lymphoma (MCL) using the recommended Phase II dosing of 27 mg/m 2 twice weekly for 2 of every 3 weeks. Primary objective was objective response rate (ORR). Nineteen patients were accrued (7 CLL, 12 MCL). Four CLL patients achieved stable disease (SD). Two MCL patients achieved partial response (PR), and 6 had SD. One additional MCL patient with SD subsequently achieved PR 9 months after completion of AT7519M. Tumor lysis syndrome was not reported. In conclusion, AT7519M was safely administered to patients with relapsed/refractory CLL and MCL. In CLL, some patients had tumor reductions, but the ORR was low. In MCL, activity was noted with ORR of 27%.